2022
DOI: 10.1002/aoc.6824
|View full text |Cite
|
Sign up to set email alerts
|

A novel Fe3O4@TCH@Ni(II) nanoparticle: An efficient magnetically retrievable nanocatalyst for C–C and C–heteroatom bond formation reaction

Abstract: Layered Ni(II) complex on magnetic nanoparticle as heterogeneous, efficient, novel, green, and reusable catalyst was used to cross‐coupling reaction, including carbon–carbon, carbon–nitrogen, and carbon–oxygen formations. The covalent functionalization of organic ligand, thiocarbohydrazide (TCH), on the surface of magnetic nanoparticle (Fe3O4) was determined that leading to an exceptional adsorptive ability for supporting Ni(II). The magnetic nano‐composite was characterized and investigated by using Fourier‐t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Despite the considerable prospects of palladium catalysts in cross-coupling reactions, the high cost and possible toxicity of Pd have remained a scientific challenge, highlighting the need for developing and discovering alternative ways with an environmentally friendly and non-toxic catalytic system 12 14 . Numerous studies have reported the use of other transition metals, such as Ni 15 , 16 , Cu 17 , 18 , Fe 19 , 20 , and Co 21 , 22 for more appropriate, cost-effective, and safe approaches for cross-coupling reactions, over the past decade. Considerable attention has been given to copper catalysis, owing to its good functional group tolerance, the low cost of the catalysts, and low toxicity 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Despite the considerable prospects of palladium catalysts in cross-coupling reactions, the high cost and possible toxicity of Pd have remained a scientific challenge, highlighting the need for developing and discovering alternative ways with an environmentally friendly and non-toxic catalytic system 12 14 . Numerous studies have reported the use of other transition metals, such as Ni 15 , 16 , Cu 17 , 18 , Fe 19 , 20 , and Co 21 , 22 for more appropriate, cost-effective, and safe approaches for cross-coupling reactions, over the past decade. Considerable attention has been given to copper catalysis, owing to its good functional group tolerance, the low cost of the catalysts, and low toxicity 23 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] Also, according to the studies, magnetic nanocatalysts can be reused more than conventional catalysts. 36,37 Because of their high surface area, they generally exhibit higher catalytic activity than conventional heterogeneous acid catalysts. 38 In this research and following our continuing efforts on the synthesis of catalysts, 39 we would like to introduce the logical design, synthesis, and identification of the Fe 3 O 4 @CPTMS@Asp@Ni as an efficient heterogeneous catalyst and then was probed the performance of this novel nanocatalyst to promote the synthesis of acridine derivatives 4a-p by mixing aryl glyoxals 1a-h, cyclic 1,3-dione 2a,b and ammonium acetate (3) condensation under green condition (Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, developing and discovering alternative ways with a better environment-friendly and non-toxic catalytic system is necessary. Many studies have been reported about using other transition metals, such as Ni 13,14 , Cu 15,16 , Fe 17,18 , and Co 19,20 , over the past decade. They are reported as more appropriate, cost-effective, and safe approaches for cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%